(untitled) (Modern Problems of Metallurgy, 2024)
Presented are the results of research on determining the effect of modification of the secondary aluminum casting alloy of the Al-Si system with highly dispersed silicon carbide of the F1200 brand with a particle size of 1-3 μm in the amount from 0.1 to 0.3 wt.% on the density of the cast metal and the macrostructure of cylindrical castings with a height of 150 mm and with an average diameter of 50 mm, obtained by casting in a metal mold and in a sand-clay mold with the addition of highly dispersed silicon carbide. Studies of the metal density of castings poured into a metal mold and a sand-clay mold, carried out using hydrostatic weighing of samples on analytical balances, showed the presence of the influence of modification and thermophysical conditions of solidification on the relevant indicators. In the metal form, the rate of solidification of the alloy is higher and the structure becomes denser (the alloy density of the castings obtained in the sand-clay mold is 2.7% lower compared to the castings obtained in the metal mold). The alloy with the addition of 0.1% SiC and poured into a metal mold has the highest density. In samples of castings that were cast in a sand-clay mold, with an increase in the amount of SiC, there is almost no significant change in the density of the alloy. The obtained data also indicate that both the method of obtaining castings and modification of the alloy affect its macrostructure. In particular, the macrostructure of the cast secondary alloy of the Al-Si system, which was not subjected to modification and poured into the mold, has a small shrinking sink and scattered porosity throughout the volume of the casting metal and corresponds to the 3rd point on the reference scale. The macrostructure of castings modified with highly dispersed silicon carbide includes a concentrated deep shrinking sink with coarse cracks in the lower part of the shell. As well as concentrated shrinkage porosity in the upper part of the casting. There are no macrodefects in the lower part of the casting. In general, the macrostructure of castings with 0.1-0.3 wt.% SiC, poured into the mold, corresponds to the 2nd and 3rd sparring points on the reference scale. Studies of the macrostructure of castings cast in a sand-clay mold with silicon carbide modification of 0.1% and 0.3 wt.% showed the presence of concentrated shrinking sink in the upper part of the castings and the presence of gas pores on the side surface, which corresponds to the 1st point for reference scale. The analysis also showed that they do not have a pronounced concentrated shrinking sink and all porosity is concentrated on the outside of the casting, while in the upper part of both castings there is a small concentrated porosity.